Observation of gate-controlled spin-orbit interaction using a ferromagnetic detector - Park, Youn Ho; Jang, Hyun Cheol; Koo, Hyun Cheol; Kim, Hyung-jun; Chang, Joonyeon; Han, Suk Hee; Choi, Heon-Jin (AMER INST PHYSICS, 2012)
From the Shubnikov-de Haas oscillation, estimation of the spin-orbit interaction parameter is possible only for very low temperature. An alternative method available for much wider temperature range is utilizing the ferromagnetic electrode which contacts the quantum well channel and reads the Fermi level of spin-up and -down subbands. The amount of spin-subband shift is controlled by a gate electric field and finally the spin-orbit interaction induced by Rashba effect is obtained near room temperature. At T = 150 K, a gate voltage shifts the spin subband potential and changes the spin-orbit interaction parameter by 23%. (C) 2012 American Institute of Physics. [doi:10.1063/1.3677936]
Keywords: TRANSPORT; SILICON; FIELD